KONSEP UJARAN SERUAN DALAM BAHASA MINANGKABAU: SEBAGAI DASAR PEMBANGUNAN KARAKTER BANGSA - Leni Syafyahya (Universitas Andalas, 2017)
The purpose of this paper is to explain the forms and the distribution of the form and meaning of the utterance of the cry in the Minangkabau language. The method used in data collection, the method of referring and the method of ably. Data analysis method used is method of padan. In addition, the data analysis phase is also done ie editing and coding. Based on the analysis, Ujaran appeal in Minangkabau language has a complete form and form is not complete. The complete form is built on the same model as the interrogative utterances and uses the same unfiliar particles as the exclamation. Only a different intonation, here marked with an exclamation mark at the end of speech. The shape is not lengakp is a shortened form into an exclamation / interjection. The form can be understood in a context and an exclamation mark is placed directly after the interjection, which is usually placed at the beginning of the utterance. The interjections include the shouting, curse, swearing and calling of the two forms, there is a call to seek a friend who refers to a positive attitude and there is a call to seek an opponent that refers to a negative attitude. In addition, both complete and incomplete forms have donotative meanings and connotative and emotive meanings. The denotative meaning is contained in the expression of the complete form and form of shout and form of attention. However, the incomplete form of screaming and calling attention sometimes also means emotive connotative and meaning. the meaning of the meaning depends on the context it enters. The expression of the call for incomplete forms of curse and curse is always meaningful connotative.Keywords: speech, form, meaning, and Minangkabau